2022
DOI: 10.3390/ijms23010553
|View full text |Cite
|
Sign up to set email alerts
|

Indigo Pulverata Levis (Chung-Dae, Persicaria tinctoria) Alleviates Atopic Dermatitis-like Inflammatory Responses In Vivo and In Vitro

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease associated with a type 2 T helper cell (Th2) immune response. The IndigoPulverata Levis extract (CHD) is used in traditional Southeast Asian medicine; however, its beneficial effects on AD remain uninvestigated. Therefore, we investigated the therapeutic effects of CHD in 2,4-dinitrochlorobenzene (DNCB)-induced BALB/c mice and tumor necrosis factor (TNF)-α- and interferon gamma (IFN)-γ-stimulated HaCaT cells. We evaluated immune cell infiltration, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…As AD pathogenesis shares common features with allergic diseases, such as pro-inflammatory immune responses ( Akdis et al ., 2006 ; Bantz et al ., 2014 ), various anti-inflammatory immune regulators from the natural extracts of medicinal plants have shown therapeutic potentials in AD ( Ku et al ., 2018 ; Song et al ., 2019 ; Bai et al ., 2020 ). Notably, from the previous studies, we understand that a common mode of action of natural products exists, i.e., by suppression of MAPKs and NF-κB ( Chen et al ., 2020 ; Min et al ., 2022 ; Zhang et al ., 2022 ). Thus, by using NJK14047, a potent and specific p38 MAPK inhibitor, for the first time, we recognized the importance of p38 MAPK inhibitors to develop novel anti-AD drugs because p38 MAPK inhibition distinctly leads to the suppression of the immune responses of AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As AD pathogenesis shares common features with allergic diseases, such as pro-inflammatory immune responses ( Akdis et al ., 2006 ; Bantz et al ., 2014 ), various anti-inflammatory immune regulators from the natural extracts of medicinal plants have shown therapeutic potentials in AD ( Ku et al ., 2018 ; Song et al ., 2019 ; Bai et al ., 2020 ). Notably, from the previous studies, we understand that a common mode of action of natural products exists, i.e., by suppression of MAPKs and NF-κB ( Chen et al ., 2020 ; Min et al ., 2022 ; Zhang et al ., 2022 ). Thus, by using NJK14047, a potent and specific p38 MAPK inhibitor, for the first time, we recognized the importance of p38 MAPK inhibitors to develop novel anti-AD drugs because p38 MAPK inhibition distinctly leads to the suppression of the immune responses of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the effectiveness of traditional Chinese medicines and their active components in treating AD ( Chen et al ., 2020 ; Min et al ., 2022 ; Zhang et al ., 2022 ). Interestingly, suppression of AD by traditional Chinese medicines has been reported to be mediated through the inhibition of mitogen-activated protein kinases (MAPKs), such as, ERK, JNK, and p38 MAPK, and NF-κB components, such as p65 ( Chen et al ., 2020 ; Min et al ., 2022 ; Zhang et al ., 2022 ). In fact, overexpression of MAPK mRNA in the skin tissue was observed in the AD group ( Chen et al ., 2020 ; Min et al ., 2022 ; Zhang et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with atopic dermatitis, the sensitivity to gentamicin was 99.7%. Fusidic acid is reported to have advantages over other anti-bacterials (Min et al, 2022) There are several combinations of antibiotics and topical corticosteroids as combination therapy in patients with atopic dermatitis. According to studies, the best combination is a topical corticosteroid with fusidic acid.…”
Section: Discussionmentioning
confidence: 99%
“…2), mainly as its sulfonic salt, indigo carmine ( Figure 1 ). Additionally, further research has emerged for its application in the development of eco-friendly organic semiconductors [ 5 , 6 ], and has demonstrated its positive effect in traditional Chinese medicine to treat psoriasis and other inflammatory diseases [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%